The decivilizing effects of the financial system - Ampudia de Haro, F. (Human Figurations: Long-term Perspectives on the Human Condition, 2017)
This paper focuses on the financial system as a global figuration in order to analyse its social logic of functioning and its connections with certain models of sociability and behaviour. As a global figuration, the financial system can be considered the result of the confluence of a triple vector of forces: a) the formation of competition spirals; b) the constitution of a complex web of interdependences and c) the constitution of a set of limits for the action of external constraints over the participants in the name of financial self-regulation. This triple vector is related to a model of sociability and behaviour based on a) the social production of indifference; b) the logic of the free-rider and c) the promotion of dis-identification patterns between the financial established and the financial outsiders. In sum, this paper proposes a framework of a figurational approach to the financial system, both in its macro- and micro-sociological dimensions.